2022
DOI: 10.1109/access.2022.3207488
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Hosting Capacity Assessment of Distribution Systems With Multitype DERs Using Analytical OPF Method

Abstract: Renewable energy is being increasingly integrated into distribution systems worldwide in response to technological, economic, and environmental challenges. The assessment of hosting capacity allows us to determine the maximum installation capacity of distributed energy resources (DERs) in a distribution system within its operational limits to obtain more benefits. In this study, a new multistage algorithm is developed based on an analytical approach and optimal power flow (OPF) for the assessment of DERs' host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Based on the time-varying generations and demands from measurement devices, and historical data, the time series methods are applied easily in short-term timescales to avoid increasing complexity or computational times [93]. Various recent articles applied these approaches for estimating the DSF [94][95][96][97][98][99][100][101].…”
Section: Conventional Approachesmentioning
confidence: 99%
“…Based on the time-varying generations and demands from measurement devices, and historical data, the time series methods are applied easily in short-term timescales to avoid increasing complexity or computational times [93]. Various recent articles applied these approaches for estimating the DSF [94][95][96][97][98][99][100][101].…”
Section: Conventional Approachesmentioning
confidence: 99%
“…Wang et al [16] showed that the risk of system voltage is reduced through the allocation of VaR capacity of inverters in an economical way. Hassan et al [17] proposed the evaluation of network hosting capacity to integrate the maximum installed capacity of DERs in a distribution system by observing the operating range. The work presented in [18] dealt with the methods of evaluating and upgrading the hosting capacity of the distribution network through a comprehensive review of various research studies and practical projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the loading constraints are modeled by Equations ( 17)- (22). According to (17), a transformer's loading must not violate a specified limit, which is, from the authors' experience, about 80% of its rating. W ty is the rating of DT t at Year y, which is obtained as (18).…”
Section: Operational Constraintsmentioning
confidence: 99%
“…Despite the simplifications of the network model and size to fit in the optimization formulation, it is time-consuming and impractical for large-scale feeders with single-or twophase laterals and split-phase LV systems. Similarly, the authors in [19] propose an optimal power flow formulation to estimate the HC with multitype distributed energy resources, only validated in small test systems.…”
mentioning
confidence: 99%